Enriched circulating and tumor-resident TGF-β+ regulatory B cells in patients with melanoma promote FOXP3+ Tregs. (31st December 2022) - Harris, Robert J; Willsmore, Zena; Laddach, Roman; Crescioli, Silvia; Chauhan, Jitesh; Cheung, Anthony; Black, Anna; Geh, Jenny L. C.; MacKenzie Ross, Alastair D; Healy, Ciaran; Tsoka, Sophia; Spicer, James; et al.
ABSTRACT: B cells are emerging as key players of anti-tumor adaptive immune responses. We investigated regulatory and pro-inflammatory cytokine-expressing B cells in patients with melanoma by flow cytometric intracellular cytokine, CyTOF, transcriptomic, immunofluorescence, single-cell RNA-seq, and B:T cell co-culture analyses. We found enhanced circulating regulatory (TGF-β + and PD-L1 + ) and reduced pro-inflammatory TNF-α + B cell populations in patients compared with healthy volunteers (HVs), including lower IFN-γ + :IL-4 +  and higher TGF-β + :TNF-α + B cell ratios in patients. TGF-β-expressing B cells in the melanoma tumor microenvironment assembled in clusters and interacted with T cells via lymphoid recruitment (SELL, CXCL13, CCL4, CD74) signals and with Tregs via CD47:SIRP-γ, and FOXP3-promoting Galectin-9:CD44. While reduced in tumors compared to blood, TNF-α-expressing B cells engaged in crosstalk with Tregs via TNF-α signaling and the ICOS/ICOSL axis. Patient-derived B cells promoted FOXP3 + Treg differentiation in a TGF-β-dependent manner, while sustaining expression of IFN-γ and TNF-α by autologous T-helper cells and promoting T-helper cell proliferation ex vivo, an effect further enhanced with anti-PD-1 checkpoint blockade. Our findings reveal cytokine-expressing B cell compartments skewed toward regulatory phenotypes in patient circulation and melanoma lesions, intratumor spatial localization, and bidirectional crosstalk between B and T cell subsets with immunosuppressive attributes.